ANALISA KEKUATAN AGREGAT KLAS B MATERIAL KABUPATEN SOLOK - Masril, Masril (Ensiklopedia of Journal, 2025)
Class B aggregate, which is usually better known as LPB which is used for the lower foundation layer, is carried out spread along the road on top of the selected embankment or on the surface of the prepared road body. In planning the thick pavement structure that needs to be considered is the function of the network, plan age, average daily traffic, DDT, FR, IP, Equivalent Number, ITP and relative strength coefficient.The implementation of road construction planning must also pay attention to the materials used, because it will determine the quality of the road construction, so the road foundation material greatly affects the quality and durability of road construction, in the implementation of road construction planning we recognize the top foundation layer and the bottom foundation layer. In the implementation of this implementation, testing of Class B material for the lower foundation or LPB originating from the solok district is carried out, the test is carried out is the specific gravity, moisture content of the aggregate, compaction and determines the CBR value of the Plan From the results of the implementation of the Class B mateial test for the sample of the number of collisions 65 x 5 obtained the value of moisture content = 5.99%, dry density 2.209. CBR prices of 51.7 and 98.9. Class B mateial testing for 30 x 5 impact number samples obtained moisture content value = 6.00%, dry density 2.084. CBR price 30 and 64.4. Class B mateial testing for Sample number of impact 10 x 5 obtained water content value = 6.12%, dry density 1.941. The CBR price is 16.7 and 44.4 and the resulting Plan CBR value at % gd is 98%, and the CBR at 95% gd is 45%.From the above test results, it can be concluded that Class B coarse aggregate from Solok can be used for Class B base in road construction works. Keywords: Aggregate Base Class B  for Roads